A hierarquia dos tratados internacionais de direitos humanos no ordenamento jurídico brasileiro - Zamlutti Júnior, René (2011)
The study aims to examine, in light of the new feature that came to adopt the Constitutions from the second half of the twentieth century, and constitutionalism that would result, the way the Brazilian legal system receives the international treaties that deal with human rights. For this, it will seek, first, to demonstrate how fundamental rights and human dignity became the center of the constitutions of democratic states of Western law, as a consequence of the facts found by the end of World War II. The following will analyze the phenomenon of internationalization of the protection of fundamental rights. Finally, it will be presented the way that Brazilian Constitutions followed in dealing with international treaties on human rights as well as the possibility of contradictions between domestic legislation and international law, the remedies that Brazilian doctrine and the Judiciary, especially the Brazilian Supreme Court, presented to over time to such issues, and analysis about the correctness of such solutions. Finally, it will be sought to point a constitutional exegesis Brazilian light the greatest possible protection of human rights, through a systematic interpretation of the Constitution